Potensi brand personal identity dalam keputusan pembelian konsumen generasi Z pada produk H&M di Indonesia - Asrini, Wayan; Pratisti, Cahyani (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2024)
This research aimed to investigate a broader perspective regarding a customer's perceived value through indicators and fashion involvement towards its purchasing decisions with brand personal identity as a moderating variable. Using quantitative research with an associative approach, the research sample of H&M consumers in Indonesia aged 16- 27-year-old male and female, and have purchased products wether offline or online, as many as 119 respondent, Samples were taken using purposive sampling technique. Data analysis method used Structural Equation Modeling - Partial Least Square (SEM-PLS). The results showed that customer perceived value and fashion involvement partially affected brand personal identity. Brand personal identity affected buying decisions. Customer perceived value and fashion involvement partially affected buying decisions mediated by the brand’s identity. This research implied H&M to increase customer perceived value, fashion involvement, and brand personal identity of the product through maintaining consistent product quality, offering appropriate prices with product quality.